ANALISIS PENGARUH KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN AIS PRODUCT DI KABUPATEN PURWOREJO - Kuswadi Rustam; Damar Eko Cahyono; Alief Indita Agustiani (Sekolah Tinggi Ilmu Ekonomi SBI, 2025)
Ais Product is a household business engaged in bamboo and broom handicrafts. In this business the company is engaged in production and sales. The progress of Ais Product's business depends on the quality of the product, the planning of the products produced by the company must be truly in accordance with the needs of consumers. This is to be in accordance with the objectives of the company where the products produced can be accepted and in accordance with consumer needs and can satisfy consumers. This study aims to analyze the effect of Product Quality, Price, and Promotion on Purchasing Decisions on Ais Products. This study uses a method that is